NEBIVOLOL and the 2009 ESH update to the 2007 ESH/ESC Guidelines - V. I. Makolkin (Кардиоваскулярная терапия и профилактика, 2010)
The paper discusses the position of beta-blockers, nebivolol in particular, in the Reappraisal 2009 of ESH/ESC Guidelines on arterial hypertension (AH) management. Nebivolol is not only highly selective towards beta-1 angiotensin II receptors, but also metabolically neutral, and therefore, could be used in AH patients with metabolic disorders.